The results of serum agglutination (wright) and Rose-Bengal tests ın the diagnosis of brucellosis: 6 years retrospective seroepidemiological evaluation of Cerrahpasa Medical Faculty serology laboratory datas Abstract - Çelik, Deniz Gözde; Sirekbasan, Serhat; Abdelkareem, Ali; Yüksel, Pelin; Aslan, Mustafa; Sarıbaş, Suat; Ziver, Tevhide; Çakan, Hüseyin; Kocazeybek, Bekir (Cerrahpaşa Medical Journal, 2019)
Objectives: Brucellosis is a zoonotic infectious disease caused by Brucella organisms and widespread all over the world as in Turkey. We aimed to evaluate the brucellosis seroepidemiology by investigating retrospectively the serological markers of brucellosis (Wright aggluti-nation and Rose Bengal tests) of serum samples of 4,344 patients who were applied to our laboratory with brucellosis suspection in Istanbul and its surroundings for 6 years period. Methods: 4,344 sera samples of patients with brusellosis suspection who were applied to the serology laboratory of Cerrahpasa Medical Faculty Medical Microbiology Department from various clinics were included in this study between November 2003-December 2011. In these sera samples Wright Test were performed by using conventional sera agglutination test principles, Rose Bengal test were performed by slide agglutination test principles. In addition, seroepidemiological parameters (age, gender, nutrition habits, living in urban or rural areas, disease state of other individuals between the family and seasonal distribution) were evaluated in this retrospective analysis. Results: Brusellosis seropositivity was detected as 3% in 128 of 4,344 cases by Wright and Rose-Bengal tests. 88 (69%) and 40 (31%) of the 128 cases were detected positive in ≥160 and <1/160-1/120 titers by Wright method, respectively. 71(55%) and 57(45%) of the 128 cases were female and male, respectively. The most frequent positivity was detected in 47-67 age group. The most seasonally frequent positive results for brucellosis was detected in July of summer season as 18 cases and the consumption of home-made dairy products and raw milk were responsible for the 75 brucellosis cases. While 67 cases were detected in rural life, brucellosis was detected more than one individual between the family in 43 cases. On the other hand, laboratory infections were responsible for 3 cases. Conclusion: Brusellosis seroprevalans can be considered as 3% by anaysing retrospectively the recorded datas of our center in Istanbul and its surroundings. Our seroprevalance value is higher than the 2.4% sreoprevalance value of Marmara region reported in 2006. We deter-mined similiar results in accordance with the other results in paralel to risk parameters such as the raw milk and raw milk products usage, to live in rural areas, the seasonal frequency in Summer and Spring seasons and laboratory originated transmission in this retrospective eval-uation.